Malnutrition prevalence among children and women of reproductive age in Mexico by wealth, education level, urban/rural area and indigenous ethnicity. (9th August 2020) - Batis, Carolina; Denova-Gutiérrez, Edgar; Estrada-Velasco, Bárbara I; Rivera, Juan
Abstract: Objective: To compare the prevalence of malnutrition (undernutrition and excess weight) by wealth, education level, ethnicity and urban/rural areas in Mexican children and women of reproductive age. Design: We compared the prevalence of overweight, obesity, wasting/underweight, stunting/short stature and anaemia by socioeconomic and ethnic indicators. For each indicator, we estimated prevalence ratios (PR) adjusted by all other socioeconomic and ethnic indicators. We analysed if results differed by urban/rural areas. Setting: Mexican National Health and Nutrition Survey 2012. Participants: Children <5 years, non-pregnant women 11–19 years and non-pregnant women 20–49 years ( n 33 244). Results: In most age groups, belonging to non-indigenous households, with high wealth, high education and in urban areas were inversely associated with stunting or short stature (PR ranging from 0·40 to 0·83), and wealth and education were inversely associated with anaemia (PR ranging from 0·53 to 0·78). The prevalence of overweight was similar across subgroups among children <5 years; however, among women 11–19 years, wealth, non-indigenous household and urban areas were positively associated (PR ranging from 1·16 to 1·33); and among women 20–49 years, education was inversely associated (PR 0·83). Conclusions: Socially disadvantaged populations have a higher prevalence of undernutrition, whereas the prevalence of excess weight is either equal (children <5 years), slightly lower (women 11–19 years) or even higher (women 20–49 years) with lower education. These results highlight the need for specific actions to address social inequalities in malnutrition in the Mexican population.